FUNGSI-FUNGSI MANAJEMEN DI PERPUSTAKAAN MADRASAH - Sopwandin, Iwan; Nurmila, Nina; Hidayat, Wahyu (Perkumpulan Sarjana Manajemen Pendidikan Islam Indonesia, 2019)
This study aims to reveal the application of the functions of management in managing libraries in madrasas. The location of the research was Madrasah Aliyah Negeri 2 Tasikmalaya, West Java. This study uses a qualitative approach. The type of qualitative research used a case study. Data were collected through observation, interviews and documents analysis. The results of the study show that the functions of management applied in managing the madrasah library include (1) preparation of the program; (2) implementation which is essentially service; (3) supervision carried out by Madrasah Heads and Library Heads, and; 4) evaluation. The functions of management that were applied in madrasah library management are relatively the same as the implementation of school library management functions in general. There was nothing typical of madrasa library management. It means that theoretically and practically there are no distinguishing factors in the application of the functions of management in managing madrasa libraries with library management in public schools. So, there are needs to be a reconstruction of the management theory of Islamic education that is completely different from the management theory of education in general.